Noise exposure during early development influences the acoustic startle reflex in adult rats - Rybalko, Natalia; Bureš, Zbyněk; Burianová, Jana; Popelář, Jiří; Grécová, Jolana; Syka, Josef (Physiology & behavior, 2011)
Noise exposure during the critical period of postnatal development in rats results in anomalous processing of acoustic stimuli in the adult auditory system. In the present study, the behavioral consequences of an acute acoustic trauma in the critical period are assessed in adult rats using the acoustic startle reflex (ASR) and prepulse inhibition (PPI) of ASR. Rat pups (strain Long-Evans) were exposed to broad-band noise of 125 dB SPL for 8 min on postnatal day 14; at the age of 3-5 months, ASR and PPI of ASR were examined and compared with those obtained in age-matched controls. In addition, hearing thresholds were measured in all animals by means of auditory brainstem responses. The results show that although the hearing thresholds in both groups of animals were not different, a reduced strength of the startle reflex was observed in exposed rats compared with controls. The efficacy of PPI in exposed and control rats was also markedly different. In contrast to control rats, in which an increase in prepulse intensity was accompanied by a consistent increase in the efficacy of PPI, the PPI function in the exposed animals was characterized by a steep increase in inhibitory efficacy at low prepulse intensities of 20-30 dB SPL. A further increase of prepulse intensity up to 60-70 dB SPL caused only a small and insignificant change of PPI. Our findings demonstrate that brief noise exposure in rat pups results in altered behavioral responses to sounds in adulthood, indicating anomalies in intensity coding and loudness perception.
Keywords: akustická stimulace; úleková reakce; Animals; Rats; Hearing Tests; sluchové kmenové evokované potenciály; Female; kritické období (psychologie); Acoustic Stimulation; ženské pohlaví; Rats, Long-Evans; hluk; Auditory Perception; sluchová percepce; potkani Long-Evans; sluchové testy; inhibice (psychologie); krysa rodu Rattus; Reflex, Startle; zvířata; Inhibition, Psychological; Evoked Potentials, Auditory, Brain Stem; Noise; Critical Period, Psychological